1997
DOI: 10.23986/afsci.72798
|View full text |Cite
|
Sign up to set email alerts
|

The effects of added glycerol or unprotected free fatty acids or a combination of the two on silage intake, milk production, rumen fermentation and diet digestibility in cows given grass silage based diets

Abstract: The addition of glycerol or free fatty acids either alone or in combination to concentrate was studied for the effects on feed intake, milk production, rumen fermentation, blood metabolites and diet digestibility in dairy cows given grass silage ad libitum. The study was conducted on 12 mid-lactating cows, four of them ruminally cannulated. Barley-based concentrate (control diet, C) was given 7 kg/d as fed. In the other three diets, 36 g/kg of barley was replaced by glycerol (G) or a mixture of free fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
46
4
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 11 publications
18
46
4
1
Order By: Relevance
“…The tendency for increased ECM yield in cows fed high-purity glycerine is in line with results reported by Bodarski et al (2005), who observed increased milk yield in cows fed a diet supplemented with glycerine at a rate of 300 or 400 ml/day during 10 weeks of lactation. In contrast, a number of studies have found no effect of glycerine on milk yield (Khalili et al, 1997;Wang et al, 2009;Carvalho et al, 2010), and DeFrain et al (2004) observed a tendency for decreased milk yield. However, in all these studies, concentrate was replaced by glycerine, whereas in the present study glycerine was provided in addition to concentrate.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…The tendency for increased ECM yield in cows fed high-purity glycerine is in line with results reported by Bodarski et al (2005), who observed increased milk yield in cows fed a diet supplemented with glycerine at a rate of 300 or 400 ml/day during 10 weeks of lactation. In contrast, a number of studies have found no effect of glycerine on milk yield (Khalili et al, 1997;Wang et al, 2009;Carvalho et al, 2010), and DeFrain et al (2004) observed a tendency for decreased milk yield. However, in all these studies, concentrate was replaced by glycerine, whereas in the present study glycerine was provided in addition to concentrate.…”
mentioning
confidence: 94%
“…Not only in north-western Europe but also in other regions, the rations fed to lactating dairy cows are generally based on grass silage supplemented with concentrates (Khalili et al, 1997). Glycerine is an energy-rich by-product; the energy content has been estimated to be 16.2 MJ metabolisable energy (ME)/kg (Mach et al, 2009) with glucogenic properties, produced when biodiesel is manufactured from rapeseed oil (Thompson and He, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lower result found for this variable can be explained by the lower digestibility for the diet without the coproduct. Khalili et al (1997) stated that the supply of glycerol along with plants that have a high content of fatty acids (lipids) increases the digestibility of lipids, leading to the argument that the interaction of glycerol and fatty acids results in an increase in the production of MPc (Khalili et al, 1997), being a consequence of increased digestibility of lipids. Donkin et al (2009), working with glycerol levels in the diet (0, 50, 100 and 150 g/kg) of Holstein cows, found increases in the digestibility of DM (DMD), organic matter (OMD) and crude protein (CPD).…”
Section: Resultsmentioning
confidence: 99%